Effects of aerofoil, twist and wind speed on the structural response of 1D finite element model of wind turbine blade - Sharma, Tushar; Murari, V.; Shukla, K.K. (Journal of Structural Engineering, 2024)
A method to determine static and free vibration responses of Wind Turbine Blade (WTB) is proposed. One Dimensional Finite Element Wind Turbine Blade (1DFEWTB) model is developed using thin-walled beam theory coupled with PreComp tool and the Blade Element Momentum (BEM) theory and implemented to calculate aerodynamic loading. The 9.2m long WTB is chosen for the study and the effect of different parameters such as aerofoil, twist variation and wind operating speed on the response and on estimated power generated by blade are computed. The results from the 1D model (developed using MATLAB) are in good agreement with that of 3D model (developed using Ansys and NuMAD) and are found to be efficient, fast and yet accurate for realistic WTB analysis.